Relationship between right and left ventricular function in candidates for implantable cardioverter defibrillator with low left ventricular ejection fraction. Issue 2 (31st August 2016) - Jimenez‐Juan, Laura; Karur, Gauri R.; Connelly, Kim A.; Deva, Djeven; Yan, Raymond T.; Wald, Rachel M.; Singh, Sheldon; Leung, General; Oikonomou, Anastasia; Dorian, Paul; Angaran, Paul; Yan, Andrew T.
Abstract: Background: Indications for the primary prevention of sudden death using an implantable cardioverter defibrillator (ICD) are based predominantly on left ventricular ejection fraction (LVEF). However, right ventricular ejection fraction (RVEF) is also a known prognostic factor in a variety of structural heart diseases that predispose to sudden cardiac death. We sought to investigate the relationship between right and left ventricular parameters (function and volume) measured by cardiovascular magnetic resonance (CMR) among a broad spectrum of patients considered for an ICD. Methods: In this retrospective, single tertiary‐care center study, consecutive patients considered for ICD implantation who were referred for LVEF assessment by CMR were included. Right and left ventricular function and volumes were measured. Results: In total, 102 patients (age 62±14 years; 23% women) had a mean LVEF of 28±11% and RVEF of 44±12%. The left ventricular and right ventricular end diastolic volume index was 140±42 mL/m 2 and 81±27 mL/m 2, respectively. Eighty‐six (84%) patients had a LVEF <35%, and 63 (62%) patients had right ventricular systolic dysfunction. Although there was a significant and moderate correlation between LVEF and RVEF ( r =0.40, p <0.001), 32 of 86 patients (37%) with LVEF <35% had preserved RVEF, while 9 of 16 patients (56%) with LVEF ≥35% had right ventricular systolic dysfunction (Kappa=0.041). Conclusions: Among patients being considered for an ICD, there is a positive but moderate correlation between LVEF and RVEF. A considerable proportion of patients who qualify for an ICD based on low LVEF have preserved RVEF, and vice versa.